Functional and Aesthetic Outcomes Following Spreader Graft Placement in Deviated Noses: A 5 Year Experience - Zameer Abbas Mir, Hamid Hussain Ansari, Hussan Birkhez Shami, Saadia Nosheen Jan, Farid Ahmed Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To describe the functional and aesthetic outcome following rhinoplasty using spreader grafts in post traumatic deviated noses. Design: Rretrospective cohort study Place and duration of study: July 2017 to August 2022 Methods A retrospective data analysis of patients was done who had undergone Rhinoplasty for post traumatic deviated noses using spreader grafts from July 2017 to August 2022. Patients undergoing revision rhinoplasty, incomplete description of preoperative deformities and per operative maneuvers to correct the deformities, and incomplete photographic record were excluded. The study population consisted of 11 female patients and 19 male patients. Mean (Standard Deviation) age of the patients was 30 (8) years (range 16-48 years). The follow up post-operatively was from 12 - 26 months (mean, 15±3 months). Postoperative aesthetic outcome was assessed by the patient him/her self and 2 independent surgeons using pre and postoperative photographs. Functional outcomes and complications were also evaluated. Results: Study by two plastic surgeons found that out of the total 30 patients 22 had no post operative residual deformity, 7 had residual deformity not requiring revision and only 1 patient had a residual deformity that would require revision surgery. The patient outcome showed that out of the total 30 patients 20 were satisfied with their postoperative result, 9 thought that their postoperative nose was better than their preoperative nose and 1 patient was dissatisfied with the postoperative result. Over all the obstructive symptoms improved after surgery and only two patients complained of unilateral partial nasal obstruction at one year follow up. No complication occurred in any patient. Practical implication Conclusion: We conclude that the use of spreader graft as we have achieved good functional as well as precise aesthetic results, without recurrence of the problem. his will open new gateways in world of aesthetics and reconstruction . Keywords: Spreader grafts, nasal valve collapse, deviated nasal septum, post operative assessment.